Chemical Studies on the Structure of Mucopeptide Isolated from Streptococcus bovis - Kane, Judith (J Bacteriol, 1969)
Mucopeptides isolated from Streptococcus bovis cell walls were found to be composed of alanine, glutamic acid, lysine, and threonine in a mole ratio of 3:1:1:1. A dipeptide, N(ε)-lysylthreonine, was isolated from S. bovis mucopeptide by ion-exchange chromatography. This finding suggests that threonine is associated with the bridge which cross-links adjacent tetrapeptides by connecting the ε-amino group of lysine of one tetrapeptide to the carboxyl group of d-alanine of another to form the mucopeptide matrix.